Patterns of antibody binding to aquaporin-4 isoforms in neuromyelitis optica - Mader, Simone; Lutterotti, Andreas; Pauli, Franziska Di; Kuenz, Bettina; Schanda, Kathrin; Aboul-Enein, Fahmy; Khalil, Michael; Storch, Maria K.; Jarius, Sven; Kristoferitsch, Wolfgang; Berger, Thomas; Reindl, Markus (PLOS ONE, 2010)
Neuromyelitis optica (NMO), a severe demyelinating disease, represents itself with optic neuritis and longitudinally extensive transverse myelitis. Serum NMO-IgG autoantibodies (Abs), a specific finding in NMO patients, target the water channel protein aquaporin-4 (AQP4), which is expressed as a long (M-1) or a short (M-23) isoform.